PENGARUH BALANCE EXERCISE TERHADAP TINGKAT KESEIMBANGAN LANSIA DENGAN RESIKO JATUH TAHUN 2024 - Royani, Evi; Siska, Fera; Arlina, Zakinah (LPPM STIKes Mitra Adiguna, 2025)
Elderly individuals are at high risk of postural balance disturbances due to decreased muscle function, which increases the risk of falls. One effective method to improve body balance is balance exercise. Objective: To determine the effect of balance exercise on the balance levels of elderly individuals with fall risk at the Harapan Kita Social Welfare Elderly Home in Palembang in 2024. This study used a quantitative approach with a quasi-experimental design and a one- group pretest-posttest approach. A sample of 20 elderly participants was selected using purposive sampling. Balance was measured using the Berg Balance Scale before and after the balance exercise intervention. Data analysis was performed using parametric statistical analysis with paired t-test. The average balance level before the intervention was 40.30 (moderate fall risk), and after the intervention, it increased to 46.55 (low fall risk). The statistical test results showed a p-value of 0.000 (p < 0.05), indicating a significant effect of balance exercise on improving balance in the elderly. Balance exercise is effective in improving body balance and reducing fall risk in elderly individuals. Future research should extend the duration of the intervention and explore other methods that can support balance improvement in the elderly.